ВИВЧЕННЯ ЗАЛЕЖНОСТІ ЗВ’ЯЗКУ «СТРУКТУРА - ПРОТИЗАПАЛЬНА ДІЯ» ТА «СТРУКТУРА - АНАЛЬГЕТИЧНА ДІЯ» СЕРЕД ПОХІДНИХ АМІДІВ МАЛОНОВОЇ ТА ЩАВЛЕВОЇ КИСЛОТ - Vakhnina, N. H. (Фармацевтичний часопис, 2016)
THE STUDY OF THE DEPENDENCE RELATION "STRUCTURE – ANTI- INFLAMATORY EFFECT" AND "STRUCTURE ANALGESIC EFFECT" AMONG THE AMID DEREVATIVES OF MALONIC AND OXALIC ACIDS N. H. Vakhnina The National University of Pharmacy Nonsteroidal anti-inflammatory drugs ( NSAIDs) are widely used in clinical practice. However, all existing on the pharmaceutical market NPVS have limitations for use, contraindications and a high risk of adverse reactions. Considering this, a topical direction of modern pharmacy is the research and development of new highly effective NSAIDs with low toxicity. The aim of this work was to study the dependence relation "structure - anti-inflammatory effect" and "structure - analgesic effects" among 43 newly synthesized amid derivatives of malonic and oxalic acids. Anti-inflammatory effect was studied in terms of play Karaganov acute swelling of rats foot; analgesic activity was studied on the model of "acetic acid spasms" in rats. The studied compounds were injected intraperitoneally to experimental animals at a dose of 1/20 LD50. The comparative drug voltaren (diclofenac sodium) was administered to rats intragastrically only with one dose of 8 mg/ kg, recommended for preclinical studies, the comparative drug dipyrone ( Metamizole sodium) was administered to rats intragastrically only with one dose of 50 mg/ kg. The obtained experimental data were processed statistically using t-student criterion. When studying anti-inflammatory action,it was proved that the majority vevcani compounds detects quite weak antiekssoudativoe action. Probable anti-inflammatory activity, which was statistically significantly different from the control group pathology, was identified in three compounds under laboratory cipher No. 8, No. 16 and No. 34 and is of 32.7%, 60,4% and 28.8% respectively. Among the studied derivatives of 4-( adamantyl-1)-thiazol-2-oxalic acid amide ( compounds No. 31 to 36), the maximum antiexudative effect has the molecule under the code No. 35 (25.8%) and No. 34 (28,8%), and moreover the last has statistically significant differences with the control group pathology. The maximum ability to affect the process of acute inflammation at the level of the comparative drug of voltaren for compound No. 16 is ( di-(2,4-dimethyl) malonic acid and). The study of analgesic activity showed that compounds under the code of №6, №13, №17, №18, №29 and No. 30, which had metaxylene, modellini, methyl, cycloheximide and propanolamine radical in the main chain of the molecule do not have analgesic action. It should be noted that19 of 43 studied compounds had a powerful analgesic activity, as evidenced by the statistically significant difference in the number of "spasm" from the group of control pathology. These are the compounds under laboratory codes: №3, №4, №5, №7, №8, №9, №10, №15, №16, №23, №24, №25, №28, №32, №33, №34, №35, №39 and No. 43. The analgesic activity of these compounds was in the range of 13.1 - of 58.9%.Only two compounds No. 16 and No. 43 had no significant differences from the activity of comparative drugs of voltaren and dipyrone . It should be noted that the compound No. 16 (di-(2,4-dimethyl) malonic acid and) tends to have an over effect of the reference drugs, voltaren, 8% analgin by 12%. The obtained results allowed us to prove regularity of anti-inflammatory and analgesic activity dependence from chemical structure of molecules and to select compound No. 16 for further pharmacological studies, which showed maximum anti-inflammatory and analgesic effects. References 1. Doklinichni doslidzhennya likarsʹkykh zasobiv: metod. rek. / za red. O. V. Stefanova. – K. : Avitsena, 2001. – 528 s. 2. Prohramma statystycheskoho analyza. Rezhym élektronnoho dostupa www.analystsoft.com/ru 3. Ryeznykov O. H. Zahalʹni etychni pryntsypy eksperymentiv na tvarynakh / O. H. Ryeznykov // Endokrynolohiya. – 2003. – T. 8, № 1. – S. 142–145. 4. Chaparro M. New molecules in the treatment of inflammatory bowel disease / M. Chaparro, J.P. Gisbert //Gastroenterol Hepatol. – 2015. – Vol. 26. – R.210-215. 5. Miazina M.A. Metyrapone effect on gastroprotective action of corticotropin-releasing factor administered centrally against indomethacin-induced gastric injury/ M.A. Miazina, T.R. Bagaeva, L.P. Filaretova //Ross Fiziol Zh Im I M Sechenova. – 2014. – №100(12). – R.1421-1430. 6. Mkontwana N. Oral analgesia for relieving post-caesarean pain/ N. Mkontwana, N Novikova // Cochrane Database Syst Rev. –2015. – Vol. 29(3) . – R.450-456. 7. Seyed Mirzaei S.M. Non-Steroidal Anti-Inflammatory Drug Related Peptic Ulcer Disease in Patients Referred to Afzalipour Hospital / S.M. Seyed Mirzaei, M.J. Zahedi, S. Shafiei Pour //Middle East J Dig Dis. – 2015. – Vol.7(4). – R. 241-244.